G‘OVAK-ELASTIK ANIZOTROP MUHITDA TO‘LQINLARNING ANALITIK MODELLARINI O‘RGANISh - Quzratov, M.A. (SCIENCE and SOCIETY, 2025)
This article discusses analytical models describing the wave propagation process in a porous-elastic anisotropic medium. The wave behavior in such media is analyzed based on Biot’s theory. Wave equations are derived, dispersion relations are determined, and the influence of anisotropic medium parameters on wave propagation is evaluated.